2020
DOI: 10.32479/ijeep.10003
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Economic Growth: Evidence From Post-Communist Countries

Abstract: Current study aimed to explore the nexus between energy and economic growth in post-communist nations during 1995-2014. As an empirical model, the growth model is employed including economic complexity indicator as a measure of capabilities for exporting sophisticated products. We employ Pedroni's (1999) panel cointegration tests and Panel Dynamic OLS estimation to assess the long-term link between the variables. At 1% significance level, we confirm cointegration between energy consumption and economic growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…The most famous is calculating reliability by the average group failure rates of elements [57][58][59][60][61]. To carry out the calculation, it is necessary to know: the types of elements, the failure rate of elements of various types λ, and the number of elements of each type Ni included in the system.…”
Section: Resultsmentioning
confidence: 99%
“…The most famous is calculating reliability by the average group failure rates of elements [57][58][59][60][61]. To carry out the calculation, it is necessary to know: the types of elements, the failure rate of elements of various types λ, and the number of elements of each type Ni included in the system.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the sample size along the Eatat, we conclude that the soil has been consistently linear. Comparing the sample sizes for all linear signs (furrows), it is concluded that the soil is uniformly moist [13][14][15][16][17][18][19][20][21]. At each depth point on the plane, comparing soil moisture, we conclude that the soil moisture content and moisture level are reached.…”
Section: Methodsmentioning
confidence: 97%
“…At each depth point on the plane, comparing soil moisture, we conclude that the soil moisture content and moisture level are reached. A table is drawn up for various irrigation methods that use the UC as an indicator to determine the dependence of irrigated water consumption on the level of leveling [15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…During the growing season of cotton, before irrigation, prepare the soil for irrigation, ensure balanced consumption of water and nutrients by the plant, reduce water loss, create the most optimal irrigation system, irrigate in deserts, saline soils, and groundwater at the height of 2-3 m and the Bukhara branch of the Tashkent the Institute of Irrigation and Agricultural Mechanization Engineers and the Scientific Research Institute of Breeding, Seed Production and Cultivation of Agrotechnology of the Bukhara Scientific Experimental Station in 2018-2020 for the development of water and resourcesaving equipment, on saline soils to obtain a high and high-quality cotton harvest, at the same time, studies were carried out to test the complex unit of the palletiser -longitudinal ridge and transverse floor, and an application for a new complex unit registered for the RUz patent IPA(FAP 2021 0024) [3,4], [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Methodsmentioning
confidence: 99%